Correlates of adolescents' involvement in gambling-related behaviour in Ondo city, Nigeria: advocating educative programmes to curb the act (2023)
The study assessed the correlates of adolescents' immersion in gambling- related behaviour in Ondo city. The study adopted the survey design of correlation type. It will help to understand association between identified variables. The population of the study comprised all adolescents, who are within the age of 13 and 19 years, in Ondo city. Ondo city comprised two local government areas of Ondo West and East. Simple random sampling was used to select 800 adolescents from schools and community centres, while structured questionnaire was developed comprising validated scales to measure Variables- Media Influence r= 0.72; Childhood Experience r= 0.78); Gambling Venue Accessibility r= 0.72; Cognitive Bias r= 0.72; and Peer Influence r= 0.91; were used for data collection. Finding revealed that the rating of gambling-related behaviour among adolescents was high (x?= 2.64:2.5). Also, there are positive significant relationships between adolescents' involvement in gambling behaviour and media influence (r = -.073, p (.040) <.05); gambling venue accessibility (r=-.087*, p (.014) <.05), peer influence (r =. 110**, p (.002) <.05) but had no significant relationship with childhood experience (r = -.032, p (.370) >.05) and cognitive biases (r = -.049, p (. 171) >.05). It is recommended that there is need for implementing comprehensive educational programmes in schools and community to curb media influence, peer pressure as well as indiscriminate siting of betting centres in and around the neighbourhood.